Methylene Blue Dye Wastewater Treatment Based On Tertiary Stage of Industrial Wastewater Treatment Process: A Review - Azhar, Faiz Hafeez; Hussin, Rosniza; Ibrahim, Siti Aida; Raja Ahmad, Raja Adibah; Shohur, Muhamad Fikri (Emerging Advances in Integrated Technology, 2023)
Methylene blue (MB) is frequently used in the textile, rubber, plastics, leather, pharmaceutical, cosmetic, and food industries. As a colouring and staining agent, MB is reported as one of the most studied dyes involving degradation and photocatalytic activity. Unfortunately, the discharge of waste from the mentioned industries contains residues of dyes, whereby the presence of a very low concentration of dyes can be highly visible. Discharging the waste without suitable treatment can cause many complications for the environment and human health. Due to that reason, the control of dye wastewater has become the most challenging task. Therefore, this review article will be focused on the MB treatment process, especially membrane filtration technology involving a pressure-driven membrane process, which is reported to be the most efficient method to treat MB dye wastewater.